Cinema at the margins - Dixon, Wheeler W., 1950- (New perspectives on world cinema., 2013)
More and more, just a few canonical classics, such as Michael Curtiz's "Casablanca" (1942) or Victor Fleming's "Gone With The Wind" (1939), are representing the entire film output of an era, to a new generation that knows little of the past, and is encouraged by popular media to live only in the eternal present. What will happen to the rest of the films that enchanted, informed and transported audiences in the 1930s, 1940s, and even as recently as the 1960s? This collection of essays aims to highlight some of the lesser-known treasures of the past--those titles that have been pushed aside by today's wave of cinema amnesia